Archives, musées, monuments historiques. Quel avenir pour le patrimoine d’Alsace-Lorraine (1914-1919) ? - Joseph Schmauch (In Situ)
The beginning of the War in August 1914 put an end to a period of cultural revival in Alsace and Lorraine. It also led to renewed interrogations about the political future of these annexed provinces. From 1915, special commissions were set up in Paris in order to study the future of Alsace as a French province. They recommended the introduction to Alsace and Lorraine of French legislation on the protection of the cultural heritage, but nonetheless taking into account some specific local customs. Shortly after the Armistice, the French ministry of Fine Arts sent to the now French departments in the East a staff of architects, headed by Robert Danis, and also an archivist. Their mission was to set up a regional direction of fine arts, to solve different problems arising from the war and to give a new impulse to the local heritage services.